INVESTIGATING THE USE OF BAHASA INDONESIA (INDONESIAN) IN EFL CLASSROOM - Elfa Madani; Eka Nurhidayat; Eva Fitriani Syarifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Using the first language in teaching English has always been controversial in teaching and learning English. In Indonesia, Bahasa Indonesia is also used in many English classes. This research aims to investigate the teacher and student purposes of using Bahasa Indonesia in EFL classrooms. This research used a qualitative design with interviews and observation instruments as the data collection techniques. Participants in this research were English teachers and students at one of the senior high schools in Majalengka. The findings show that there are many purposes for teachers and students to use of Indonesian in the classroom. As long as the lecturer or teacher uses L1 correctly it can support the teaching process.